Placebo Adverse Events in Non-alcoholic Steatohepatitis Clinical Trials: A Pooled Analysis of 2, 944 Participants. (30th April 2023) - Tay, Phoebe Wen Lin; Ng, Cheng Han; Lin, Snow Yunni; Chin, Yip Han; Xiao, Jieling; Lim, Wen Hui; Lim, Sze Yinn; Fu, Clarissa Elysia; Chan, Kai En; Quek, Jingxuan; Tan, Darren Jun Hao; Chew, Nicholas; et al.
Abstract : INTRODUCTION: In the absence of an effective treatment for non-alcoholic steatohepatitis (NASH), a randomized, placebo-controlled trial (RCT) remains the current gold standard study design in NASH. As NASH is a largely asymptomatic disease, the side effects of potential therapies require careful evaluation, therefore a pooled rate of the adverse events (AEs) in placebo-treated patients serves as a useful comparator for safety. Therefore, we performed a systematic review and meta-analysis to estimate the rate of AEs among participants in the placebo arm of NASH RCTs. METHODS: Medline, Embase and Cochrane Central Register of Controlled Trials were searched to include clinical trials in phase 2–4 NASH RCTs with placebo treatment arms. A pooled proportions of AEs were analyzed using a generalized linear mixed model with Clopper-Pearson intervals. RESULTS: A total of 41 RCTs (2, 944 participants on placebo) were included in this meta-analysis. A total of 68% (confidence interval [CI] 55%–77%) of participants on placebo experienced an AE, 7.8% (5.7%–10%) experienced serious AEs and 3.1% (CI: 1.9%–5.1%) experienced AEs leading to discontinuation. A significantly higher proportion of participants experienced serious AEs in phase 3 studies compared to in phase 2 studies ( P < 0.01) and in pharmaceutical funded studies as compared to studies which were federal-funded studies ( P < 0.01). An analysis of clinical trials evaluating bile acid modulating agents determined that 10% (CI: 5.5%–18%) of participants receiving placebo developed pruritus. DISCUSSION: The present study summarizes the AEs with NASH placebo. Among participants in the placebo arm in NASH, two-third experienced an AE, and nearly 10% experienced a serious AE.